2003
DOI: 10.1038/sj.cr.7290157
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and functional characterization of the C-terminus of rice phosphatidylinositol 4-kinase in vitro

Abstract: A partial rice (Oryza sativa L.) cDNA clone, OsPI4Klc, was isolated through screening of a cDNA library constructed from tillering materials. OsPI4Klc encoded a peptide of 608 amino acids with a calculated molecular mass of 68.4 kDa. The OsPI4Klc peptide shared high homology and possessed the highly conserved domains present in most isolated cloned P14-kinases, i.e. a lipid kinase unique (LKU) domain and a catalytic (CAT) domain. A region with similarity to pleckstrin homology (PH) domain was present in OsPI4K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Analysis on A. thaliana genome identified four members of the family (two known, two putative) and studies via DNA chips indicated that expression of PI4Kα2 was relatively high in leaves though it did not change following hormone treatment or stress, while PI4Kβ1 and PI4Kβ2 were present in the normal tissues and up-regulated by auxin and down-regulated by cytokinin, respectively. Additionally, expressions of both were regulated following SA treatment and cold stress (Tab 3), in a manner similar to that seen in rice OsPI4K1 [8], which was induced by SA, suggesting the involvement of PI4K in plant wounding responses.…”
Section: Differential Expression Patterns Of Pi-involved Genesmentioning
confidence: 74%
See 1 more Smart Citation
“…Analysis on A. thaliana genome identified four members of the family (two known, two putative) and studies via DNA chips indicated that expression of PI4Kα2 was relatively high in leaves though it did not change following hormone treatment or stress, while PI4Kβ1 and PI4Kβ2 were present in the normal tissues and up-regulated by auxin and down-regulated by cytokinin, respectively. Additionally, expressions of both were regulated following SA treatment and cold stress (Tab 3), in a manner similar to that seen in rice OsPI4K1 [8], which was induced by SA, suggesting the involvement of PI4K in plant wounding responses.…”
Section: Differential Expression Patterns Of Pi-involved Genesmentioning
confidence: 74%
“…In a tightly regulated manner, these second messengers may be recycled by further phosphorylation of Ins(1, 4, 5)P 3 to Ins(1, 3, 4, 5)P 4 by Ins (1, 4, 5) P 3 3-kinase (IP3K), or dephosphorylation to Ins(1, 4)P 2 by inositol polyphosphate 5-phosphatase (IPPase). To date, most molecular characterizations, expression pattern analyses and biochemical studies have focused on key PI pathway-related proteins including PIS [5], PI4K [6][7][8], PIP5K [9][10][11][12][13], PLC [14,15], PLD [16], PLA 1 [17], PLA 2 [18,19], PI 3-kinase (PI3K) [20], IPPase [21] and inositol 1, 3, 4-trisphosphate 5/6-kinase (IP 3 5/6K) [22]. In contrast, little attention has been paid to other proteins such as inositol 1, 4, 5-trisphosphate receptor (IP 3 R) and PI transfer protein (PITP), and there are many other signal molecules yet to be investigated within this pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, besides the membrane binding, the PH domain of plant a-type PI4K is also involved in lipids binding, although the catalytic domain of OsPI4K1, a a-type PI4K, could phosphorylate PI4P in the absence of the PH domain (Kong et al, 2003). Our results demonstrate that the PPC region of b-type PI4Ks is involved in phospholipid binding, i.e.…”
Section: Discussionmentioning
confidence: 87%
“…The previously identified OsPI4K1 gene encodes a a-type PI4K (Kong et al, 2003) and the second one, named OsPI4K2 here (GenBank Acc. No.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation